Total body irradiation in a patient with fragile X syndrome for acute lymphoblastic leukemia in preparation for stem cell transplantation: A case report and literature review. (19th June 2015) - Collins, D. T.; Mannina, E. M.; Mendonca, M.
Abstract : Fragile X syndrome (FXS) is a congenital disorder caused by expansion of CGG trinucleotide repeat at the 5' end of the fragile X mental retardation gene 1 ( FMR1 ) on the X chromosome that leads to chromosomal instability and diminished serum levels of fragile X mental retardation protein (FMRP). Afflicted individuals often have elongated features, marfanoid habitus, macroorchidism and intellectual impairment. Evolving literature suggests the condition may actually protect from malignancy while chromosomal instability would presumably elevate the risk. Increased sensitivity to ionizing radiation should also be predicted by unstable sites within the DNA. Interestingly, in this report, we detail a patient with FXS diagnosed with acute lymphoblastic leukemia treated with induction followed by subsequent cycles of hyper‐CVAD (cyclophosphamide, vincristine, doxorubicin, dexamethasone) with a complete response who then was recommended to undergo peripheral stem cell transplantation. The patient underwent total body irradiation (TBI) as a component of his conditioning regimen and despite the concern of his clinicians, developed minimal acute toxicity and successful engraftment. The pertinent literature regarding irradiation of patients with FXS is also reviewed. © 2015 Wiley Periodicals, Inc.